A novel plant growth regulator B2 mediates drought resistance by regulating reactive oxygen species, phytohormone signaling, phenylpropanoid biosynthesis, and starch metabolism pathways in Carex breviculmis - Shi, Jiannan (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.